Special Employment Centres, Time Factor and Sustainable Human Resources Management in Spanish Hotel Industry: Can Corporate Social Marketing Improve the Labour Situation of People with Disabilities? - Cruz-Morato, Marco Antonio; García-Mestanza, Josefa; Dueñas-Zambrana, Carmen (Sustainability, 2021)
Background: Low-quality jobs, long working hours and difficult scheduling of hours have been usually reported in the hotel industry. The situation is more difficult for people with disabilities (PWD), even more in the COVID-19 crisis, especially in terms of labour inclusion (due to the labour discrimination usually suffered by this collective). Thus, Special Employment Centres (SEC) have been created in Spain to spread protected employment of PWD. Although they are improving the situation in the short term, the long-term impact developing sustainable employment is not clear. The objective of this paper is to analyze the Spanish situation, the possible differences between sheltered employment and the ordinary labour market, how SEC could be improving (or not) their labour situation in the hotel sector in the long term, and the potential of incorporating Corporate Social Marketing to overcome the problem. Methods: A content bibliographic analysis has been carried out according to the latest research about this topic, using a ProKnow-C methodology. Results: There seems to be two different groups of papers (supply and demand sides), being the supply side one (focused on HR practices about PWD inclusion and managers’ perceptions of workers with disabilities) more related to our research objective. Furthermore, few articles were found about SEC and Corporate Social Marketing in relation to this topic, highlighting the originality of this research approach. Conclusions: According to our bibliographic portfolio, the presence of labour discrimination in the regular market is more evident; and, in the long term, two opposite situations could be happening simultaneously: (a) SEC would be reinforcing the social stigma, hindering the labour situation of PWD; (b) SEC could be changing the social perspectives of clients and all society in a positive manner. Therefore, it would be necessary to go in-depth into the present subject, from an academic but also practical perspective, incorporating an innovative Corporate Social Marketing approach in order to shed new light on this issue and improving effective sustainable employment of PWD.